Realitas Poenyebaran Hoax Sebagai Perbuatan Hukum Di Dunia Maya - Bunga, Dewi (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
The development of the use of information technology that is so massive is utilized by internet network users to spread hoaxes. The consequences of spreading fake news are not only economic losses, but also create feelings of anxiety, take lives, divide people and even become the beginning of the rise of radicalism movements. This study aims to analyze hoaxes as legal acts in cyberspace and analyze law enforcement against the spread of hoaxes. This research is a normative juridical research that examines the construction of norms regarding hoaxes in Indonesian laws and regulations. Hoax or fake news is a real legal act even though it is done in cyberspace. The spread is very massive and even tends to be uncontrollable and difficult to find where it started. As a real legal act, this act has legal consequences as stipulated in Law Number 11 of 2008 concerning Information and Electronic Transactions. Nevertheless, digital literacy remains the main key in overcoming hoaxes.